Comparing Postcolonial Diasporas
XVI, 230 p.
Keywords: Bringing together a group of intellectuals from a number of disciplines, this collection breaks new ground within the field of postcolonial diaspora studies, moving beyond the Anglophone bias of much existing scholarship by investigating comparative links between a range of Anglophone, Francophone, Hispanic and Neerlandophone cultural contexts.